Emulsion Liquid Membrane for Malachite Green Dye Removal: Emulsion Stability Studies and Environmental Impact - Akash R. Raval; Omprakash K. Mahadwad (International Journal of Scientific Research in Chemistry, 2025)
Extraction of malachite green dye from aqueous solutions was investigated under varying experimental conditions using emulsion liquid membranes (ELMs). The study systematically explored the effects of key process variables and emulsion composition parameters on the dye transport efficiency into the ELMs. The membrane phase comprised kerosene as the diluent, with di(2-ethylhexyl) phosphoric acid (D2EHPA) employed as the carrier, SPAN 80 as the surfactant, and an internal phase of 0.5–2.0 M H2SO4 as the stripping agent. Emulsions were characterized for their internal droplet size distribution, viscosity, and interfacial tension with the external feed phase. Optimal removal of malachite green was achieved using an emulsion system containing 1.0 M H2SO4 as the internal phase (Cio), 8% v/v D2EHPA as the carrier (Cc), and 2.5% wt. SPAN 80 as the surfactant (Cs), with the feed phase maintained at pH 4.0. The emulsions were dispersed at 180 rpm with an emulsion-to-feed phase ratio yielding a holdup (h) of 12.8%. In addition to extraction efficiency, the study conducted comprehensive stability assessments, including swelling behavior over time. Stability was found to be strongly influenced by surfactant concentration and internal phase osmotic pressure. The optimized ELM formulation demonstrated minimal swelling and maintained structural integrity over extended operation, ensuring effective dye extraction and reusability potential.
Keywords: Malachite Green dye; D2EHPA; Stability; Emulsion liquid membrane; Wastewater Treatment